2009
DOI: 10.1108/17505930910964768
|View full text |Cite
|
Sign up to set email alerts
|

Young consumers' motives for using SMS and perceptions towards SMS advertising

Abstract: The purpose of this study is to examine young consumers' motives for using SMS, their SMS usage frequency, and their attitudes towards SMS advertising. Factor analysis on the motives for using SMS revealed seven factors, namely convenience, social involvement, enjoyment, escape, personal communication, economical reasons, and public expression. The findings show that convenience and economical reasons influence SMS usage frequency. Social involvement influences attitudes towards SMS advertising. Managerial imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 32 publications
0
37
1
4
Order By: Relevance
“…By contrast, researchers have found that consumers give a lukewarm response to SMS advertising, especially when used in excess (Grant and O'Donohoe, 2007). Consumers have also proven to be weary of being heavily charged to download mobile content (Phau and Teah, 2009), presenting the need for a cautious attitude in the use of SMS advertising. The variation in results of prior researches and differing opinions of scholars as to the effectiveness of SMS advertising can be explained by the notion that it seems to work differently for different market segments.…”
Section: Sms Advertisingmentioning
confidence: 99%
“…By contrast, researchers have found that consumers give a lukewarm response to SMS advertising, especially when used in excess (Grant and O'Donohoe, 2007). Consumers have also proven to be weary of being heavily charged to download mobile content (Phau and Teah, 2009), presenting the need for a cautious attitude in the use of SMS advertising. The variation in results of prior researches and differing opinions of scholars as to the effectiveness of SMS advertising can be explained by the notion that it seems to work differently for different market segments.…”
Section: Sms Advertisingmentioning
confidence: 99%
“…However, industries do use the technology in day-to-day business by sending relevant information to customers, providing invoices and adopting parcel tracking systems (Chutijirawong and Kanawattanachai, 2014;Merisavo et al, 2007;Phau and Teah, 2009). SMS advertising is currently used in a variety of markets and industries, although it is most common in the fast-moving consumer goods sector.…”
Section: Sms Advertisingmentioning
confidence: 99%
“…Jun and Lee (2007) found that characteristics of mobile technology, such as mobility, convenience, and multimedia service, were positively related to attitudes toward mobile advertising. Phau and Teah (2009) studied young consumers' motives for using short message services (SMS) and found that convenience and economical benefits significantly influenced SMS usage frequency. In addition, Nysveen et al (2005aNysveen et al ( , 2005b showed that perceived enjoyment, perceived usefulness, and perceived expressiveness had strong overall impacts on consumers' intentions to use mobile services.…”
Section: Consumer Behavior In M-commercementioning
confidence: 99%